The Effect of Working Capital Management on The Growth of Savings and Loan Business in The Osseda Faolala Women's Consumer Cooperative Nias - Foster Herwin Gulo; Dedi Irawan Zebua; Serniati Zebua; Aferiaman Telaumbanua (PT. Maju Malaqbi Makkarana, 2025)
This study analyzes the financial condition of the Osseda Faolala Perempuan Nias Consumer Cooperative during the period January 2021–December 2024, focusing on the management of current assets, short-term liabilities, and the repayment rate of member loans. Data were processed using descriptive statistics and simple linear regression to assess the cooperative's financial balance and factors influencing business growth. The classical assumption test showed that the regression model met the feasibility criteria, both in terms of normality and autocorrelation, thus the analysis results were reliable. The t-test results proved that working capital had a positive and significant effect on cooperative business growth with a significance value <0.05. The coefficient of determination (R² = 0.887) confirmed that 88.7% of the variation in business growth was explained by working capital management. This means that the more optimal the management of working capital—including current assets, short-term liabilities, and member loans—the higher the cooperative's chances of growth and development. In addition to strengthening the existing literature, this study is consistent with the findings of Winata et al. (2023) on manufacturing companies and Herawati (2023) on savings and loan cooperatives, both demonstrated the importance of working capital management to financial performance. However, these results differ from the research of Rezki Erdian et al. (2022) on the retail sector, which found that receivables had no significant effect on profitability. This difference indicates that the relevance of working capital is highly dependent on the institutional context. Overall, this study confirms that optimal working capital management is not merely an administrative issue, but a strategic factor determining cooperative business growth and improving welfare. member.